Genitourinary Fistula Experience in a Peripheral Hospital of Bangladesh - Begum, SN (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Genitourinary fistula is one of the most dreadful complications encountered in obstetrics and gynaecology and constitute a major surgical challenge for the urogynecologist. With advanced obstetric care, this fistula is rare in industrialized world but it is still a major health problem in underdeveloped countries, particularly in sub- Saharan Africa and Asia including Bangladesh. Victim of fistula become physically cripple, socially outcast, psychologically traumatized. Surgical repair is the definitive cure. A surgeon with adequate training and experience can optimize outcome of surgery by modifying techniques. Repair of vesicovaginal fistula remains a major challenge to surgeon worldwide. Aim of the study was to undertake a baseline evaluation of all genitourinary fistula cases and to share the experience of management of fistula with others. This descriptive study was conducted in the department of Obstetrics and Gynaecology, Sylhet M.A.G. Osmani MedicalCollege Hospital. A total 311 genitourinary fistula cases were admitted and managed here from July 2004 to March 2010. In this study 64.63% of the patients were between 20-35yrs of age (range 18-70yrs), 42.76% were primipara whereas 20.57% were grandmulti. Height was <145cm in 67.84% cases. Majority (80.38%) of the patients were from poor socioeconomic status; 91.63% was housewife, and 89.38% was illiterate. Obstructed labour was responsible for 86.81% of fistula. Vesico-vaginal fistula was the most common (87.46%) type of fistula and 79.43% of fistula was complex in nature. 92.10% had local repair through vaginal approach, labial fat graft was used in 44% cases. In this study out of 242 operation 85.54 %(n-207) had successful repair. Among them 75.61% patient were completely continent. Causes of failure were likely to be due to extensive scarring with loss of tissue, previous failed repair, large size of fistula and in some cases post-operative catheter problem and infection. Fistula is largely a preventable condition. More emphasis should be given on prevention of fistula by increasing community awareness, female education and empowerment, avoiding early marriage, family planning, improved maternity services, timely referral and availability of emergency obstetric care services. DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11328 J Bangladesh Coll Phys Surg 2011; 29: 207-212